2019
DOI: 10.1007/s40333-019-0098-2
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of two remote sensing models for estimating evapotranspiration: algorithm evaluation and application in seasonally arid ecosystems in South Africa

Abstract: Remote sensing tools are becoming increasingly important for providing spatial information on water use by different ecosystems. Despite significant advances in remote sensing based evapotranspiration (ET) models in recent years, important information gaps still exist on the accuracy of the models particularly in arid and semi-arid environments. In this study, we evaluated the Penman-Monteith based MOD16 and the modified Priestley-Taylor (PT-JPL) models at the daily time step against three measured ET datasets… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…The PT-JPL model has intensively been used for estimating ET worldwide and has been successfully applied over a wide range of biomes that included croplands, deciduous broadleaf forests, evergreen needle leaf forests, and grasslands, mixed forests, Savannas and open shrub-lands (Zhang et al, 2017;Shao et al, 2019; but its application and performance in orchards remains undocumented. The results from these studies showed moderate to strong relationships between observed and actual ET estimated using the PT-JPL (García et al, 2013;Ding et al, 2013;Zhang et al, 2017;Moyano et al, 2018;Shao et al, 2019;Dzikiti et al, 2019;and Gomis-Cebolla et al, 2019). This information therefore indicated that this model can be useful where detailed meteorological data are not available.…”
Section: Introductionmentioning
confidence: 82%
“…The PT-JPL model has intensively been used for estimating ET worldwide and has been successfully applied over a wide range of biomes that included croplands, deciduous broadleaf forests, evergreen needle leaf forests, and grasslands, mixed forests, Savannas and open shrub-lands (Zhang et al, 2017;Shao et al, 2019; but its application and performance in orchards remains undocumented. The results from these studies showed moderate to strong relationships between observed and actual ET estimated using the PT-JPL (García et al, 2013;Ding et al, 2013;Zhang et al, 2017;Moyano et al, 2018;Shao et al, 2019;Dzikiti et al, 2019;and Gomis-Cebolla et al, 2019). This information therefore indicated that this model can be useful where detailed meteorological data are not available.…”
Section: Introductionmentioning
confidence: 82%
“…Replacing NDVI with water consumption can better reflect the comprehensive impact of meteorological drought on vegetation. At present, the calculation methods of vegetation water consumption mainly include the area quota method [11][12][13], the phreatic evaporation method [14][15][16][17][18], the plant evapotranspiration method [19][20][21], the water balance method [22,23], the biomass method [24,25], and the calculation method based on remote sensing technology [26][27][28][29]. Because the research on vegetation water consumption in China is relatively insufficient, a method combining the potential evapotranspiration of vegetation method with the soil moisture and plant area calculation method can be applied to the desert, grassland, forests, and other ecosystems to approximate the ecological water demand of vegetation in the region with relatively comprehensive basic data [2].…”
Section: Introductionmentioning
confidence: 99%
“…Remote sensing is useful for assessment and development of measures for mitigation of the effects of global warming in relict Mediterranean fir forests. Spectral imagery has been employed for the early detection of forest pathogen infestations ( Immitzer & Atzberger, 2014 ), to estimate evapotranspiration ( Dzikiti et al, 2019 ), and to study photosynthetic activity ( De Sousa et al, 2017 ). Meanwhile, 3D point cloud data from laser scanning (LIDAR) have been employed in fire management ( Chuvieco & Kasischke, 2007 ) and to assess forest volume, biomass ( Van Ardt, Wynne & Scrivani, 2008 ), and canopy structure ( Adamic et al, 2017 ; Mura et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%